Historical and philosophical understanding of the essence and role of ethnic stereotypes in the modern world - Kurbacheva, Olga V. (Journal of the Belarusian State University. History, 2022)
The article is devoted to the historical and philosophical understanding of the ethnic stereotype in the modern global world. The relevance of the study is dictated, on the one hand, by the increasing level of anxiety and aggressiveness in the virtual and real space, the escalation of ethno-cultural tension, ethnophobia, as well as the increasing ethnic stereotyping in society. And, on the other hand, the lack of comprehensive and systematic studies of the problem of ethnic stereotypes in the context of modern collisions. In this regard, the article proposes a substantive historical and philosophical analysis of the nature of ethnic stereotypes, revealing not only the structural components and features of ethnic stereotyped thinking, but also the significance of ethnic stereotypes in diagnosing the prospects for ethnocultural interaction. The article differentiates authentic and artificially mythologised ethnic stereotypes, and also reveals the special role of the ethnic stereotype as a tool that can be used both to escalate tension and bring together ethnic and cultural communities. Two correlated levels in stereotyped perception are analysed: the cognitive and emotional-value levels, which together have a direct impact on the positive or negative connotation in ethnic stereotyping. The author substantiates the relationship between various distorted variants of ethnic self-expression in a hyperpositive and lithotised form and existing ethnic stereotypes, which manifests itself in ethnocultural deviation: ethnophobia, collective guilt, ethnofavoritism, ethnofanatism, etc. Exploring heterostereotypes, the author emphasises that in the conditions of open global boundaries, the attributed categorisation is conditional and therefore heterostereotypes will always act as a mental construct. The practical significance of the findings about the importance of timely detection of the transformation of ethnic stereotypes, which are a kind of indicator of ethno-cultural tension and affecting the prospect of ethno-cultural interaction in the modern multi-ethnic world, is emphasised.
Keywords: ethnos; ethnic community; social stereotype; ethnic stereotype; identity; autostereotype; heterostereotype; ethnophobia; ethnocultural interaction